Improving the Professional Competence of Educators Based on a Person-Oriented Approach - Kholmamatovna, Mamadaliyeva Marhabo; Ibragimovna, Julomova Sarvinoz; Panji, Khotamov Fakhriddin; Shokirovna, Kholboyeva Dilrabo (International Journal on Integrated Education, 2023)
In the article, the issues of improving the professional competence of pedagogues based on a person-oriented approach are discussed. It is noted that children's inclinations and interests, their relationship to the life around them are clearly visible in the game. That's why the game, skillfully organized by skilled teachers and parents, helps to raise a child mentally, physically and morally, and thus prepares him for life and practical activities.